2011
DOI: 10.1007/s13361-011-0181-1
|View full text |Cite
|
Sign up to set email alerts
|

Cage Structure Formation of Singly Doped Aluminum Cluster Cations AlnTM+(TM= Ti, V, Cr)

Abstract: Structural information on free transition metal doped aluminum clusters, Al n TM + (TM=Ti, V, Cr), was obtained by studying their ability for argon physisorption. Systematic size (n=5 -35) and temperature (T=145 -300 K) dependent investigations reveal that bare Al n + clusters are inert toward argon, while Al n TM + clusters attach one argon atom up to a critical cluster size. This size is interpreted as the geometrical transition from surface-located dopant atoms to endohedrally doped aluminum clusters with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
5
29
0
Order By: Relevance
“…A small concentration of Ar (2%) was added to the carrier gas to form cluster-Ar complexes. [50] After expansion into vacuum through a conical nozzle, the central part of the beam was selected by a skimmer and clusters entered the extraction region of a reflectron time-of-flight (TOF) mass spectrometer. Total fraction of Ar complexes for Au n + and PdAu n-1 + (n = 1-13) clusters observed in mass spectra is available in Figure S1 of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…A small concentration of Ar (2%) was added to the carrier gas to form cluster-Ar complexes. [50] After expansion into vacuum through a conical nozzle, the central part of the beam was selected by a skimmer and clusters entered the extraction region of a reflectron time-of-flight (TOF) mass spectrometer. Total fraction of Ar complexes for Au n + and PdAu n-1 + (n = 1-13) clusters observed in mass spectra is available in Figure S1 of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] For example, Chuang et al studied the structural properties of neutral Al n (2 < n < 23) clusters by using a genetic algorithm coupled with a tight-binding interatomic potential, and they found that the icosahedral structure of Al 13 can be served as the core for the growth from Al 14 to Al 18 ; 6 From a comprehensive density-functional analysis, Rao et al found that the geometries undergo a structural change from two dimensional to three dimensional up to Al 6 cluster, and Al 7 + , Al 7 − , Al 11 − and Al 13 − exhibit greater stability than their neighbors. 7 The geometrical and electronic properties of clusters can be changed by doping.…”
Section: Introductionmentioning
confidence: 99%
“…From the electronic structure, Al 13 cluster has 39 valence electrons, and the stability can be greatly enhanced by substituting with a different atom to form an electronic closed-shell structure. [14][15][16] Many different elements have been used as the substitutes to obtain the doped aluminum clusters with high stability, such as nonmetals (B, P), 17 transition metals (Cr, Mn, Fe, Co, Ni, Cu, Zn, Au), [18][19][20][21] alkali metals (Li, Na, K, Rb, Cs, Mg, Ca) 22,23 and tetravalent elements (C, Si, Ge, Sn, Pb). [24][25][26] For the 13-atom transition metal aluminum clusters, Al 12 Cu 18 and Al 12 Cu −20 have been extensively studied experimentally and the icosahedral Al 12 Cu with the center doping Cu atom was identified as the lowest energy candidate theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Their rich valence configuration, containing both delocalized sp states and quasilocalized and partially filled d-states, makes them a good choice to try to modify both the electronic and structural properties of the system by means of hybridization effects and the resulting bonding type and electronic charge redistribution. Examples are varied and range from the limit of extended three-dimensional systems (an example being the dilute magnetic semiconductors 1, 2 ) to extended two-dimensional nanostructures (like TM-doped graphene 3 ), quasi-one dimensional nanostructures (like TM-doped carbon nanotubes 4 ) or small free-standing clusters and nanoparticles of different host elements, 5,6 to mention here only some examples. In many cases, the electronic and structural properties of the hybrid system can be of potential use in the design of technological devices in optoelectronics, spintronics, a) Electronic mail: begonia@ubu.es and molecular electronics (control on the gap, spin-dependent transport, and half-metallicity 1 ), nanomagnetism (localized magnetic impurities and magnetic building blocks 6 ), hydrogen storage (increasing H adsorption capability 4 ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] A further interest in their study is to get insight on the key factors responsible for the atomic ordering or segregation in nanoalloys. 11,14 Recently, structural information of cationic TM-doped Al clusters Al n TM + (n = 5-35, TM = Ti, V, Cr) has been reported by Lang et al 5 Their experiment is based on the analysis of Ar adsorption on these clusters. Based on the preference of Ar to get attached to the TM atom instead of to the Al atoms, and on cluster-Ar bond dissociation energies pointing to the fact that the Ar atom is weakly bound (thus not considerably influencing the structure of the cluster), these authors were able to identify a geometrical transition from surfacelocated TM atom to endohedrally doped cage-like clusters at a critical size (depending on the dopant).…”
Section: Introductionmentioning
confidence: 99%